AYURVEDIC METHOD OF ULVA (VERNIX CASEOSA) VISHODHANAM (MALAXATION AND CLEANING) –A CRITICAL APPRAISAL (AYUSHDHARA, 2017)
“Kaumarbhritya” is one among the specialty of Ashtanga Ayurveda which deals with comprehensive care of mother and child. It takes care of different phases of women’s reproductive life and the child’s life right from conception to 16 years of age. Navajatashishuparicharya is the series of steps taken for wellbeing of a newborn which includes Prana pratyagamana (neonatal resuscitation), Ulvaparimarjana (cleaning of the vernix caseosa), Mukhavishodhana (cleaning of oral cavity), Pichudhrana (Application of tampon on head), Garbhodakavamana (clearing of neonate’s stomach), Nabhinalachedana (cutting of umbilical cord), Jata karma (birth rites), Lehana karma (licking of ghee, herbs, honey etc) Abhyanga (massage with oil), Snana (neonatal bath) and Raksha karma (protection of baby). Among above, Ulvaparimarjana is the initial step after the life is stabilized. There is a chance that new-borns lose body temperature because they are born naked and wet and are likely to develop hypothermia and its consequences particularly in winter. Taking care of a newborn is challenging especially in the first hour of life. Warm delivery room, immediate drying, appropriate clothing etc are helpful in preventing hypothermia. But malaxation and cleaning of vernix caseosa with Saindava sarpi mixture (SS mixture)  effectively helps in maintaining the thermos neutral environment of the baby. Uniqueness of this procedure, methodological and practical application, classical benefits with support of available evidences are essential to be reviewed in contemporary times to appraise their utility in current times and to revive the ancient practices.